The magnetoresistive recording heads (MRH) as a magnetic field vector detector - Mohd Ali, Borhanuddin; Moses, A. J. (Malaysian Institute of Physics, 1988)
A pair of monolithic ferromagnetic thin-film magnetoresistive recording head, MRH, (also referred to as the Chevron) has been investigated as a detector of magnetic field vector. Its application in the detection of magnetic fields in localised areas above the insulating coating on magnetized sheet steel is described. The applied magnetic field is most sensitive perpendicular to the direction of the spontaneous magnetization, Ms, of the uniaxially anisotropic MRH, but, linear biasing of the MRH means that the direction of the Ms is accordingly rotated away from the length of the MRH. This effectively changed the configuration of the MRH pair. The Chevron was employed as the magnetic field sensor for non-destructive detection of the crystal grain system in electrical steel. The result was found to be in close agreement with the actual grain structures.